2020
DOI: 10.15388/ekon.2020.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Market Pressure and Monetary Policy: The Turkish Case

Abstract: The purpose of this study is to determine the relationship between monetary policy and the exchange market pressure index in Turkey for the 2002–2018 period with monthly data. To obtain the foreign exchange market pressure index, this study uses the model developed by L. Girton and D.E. Roper and is based fundamentally on the monetary approach to exchange rate determination and the balance of payments. The calculated exchange market pressure index is in accordance with the developments lived in financial marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Siklar and Akca [30] adopted a VAR methodology and the output of the Granger causality test revealed that a unidirectional causal relationship existed between expansion in domestic credit to EMP, while there existed a bidirectional causal dynamic between EMP and interest rate differential in the model estimated. This EMP pattern signifies a devaluation of the Turkish Lira.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Siklar and Akca [30] adopted a VAR methodology and the output of the Granger causality test revealed that a unidirectional causal relationship existed between expansion in domestic credit to EMP, while there existed a bidirectional causal dynamic between EMP and interest rate differential in the model estimated. This EMP pattern signifies a devaluation of the Turkish Lira.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Katircioglu and Feridun (2011) found a unidirectional causality from domestic credits, international reserves, real money supply, budget, and current account balance to EMP. Siklar and Akca (2020) investigated the relationship between the monetary policy and EMP in Turkey, covering the period from January 2002 to December 2018. They found bidirectional causality between the interest rate differential and EMP and unidirectional causality from domestic credit to EMP.…”
Section: Relevant Empirical Literaturementioning
confidence: 99%
“…When PPP does not hold, the effect of nominal exchange rate changes is fully reflected in the real exchange rate changes. This impacts the relative prices of exports and imports, and thereby, the country's competitiveness and export earnings (Gilal, 2011). A negative exchange rate shock causes the collapse of firms and financial institutions, resulting in a loss of output and employment.…”
Section: Introductionmentioning
confidence: 99%